Urgensi Pembentukan Undang Undang Keamanan Keuangan Siber: Melindungi Sistem Finansial di Sektor Digital - Sabila Helmalia Putri (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2026)
Rapid developments related to technology are spreading rapidly in human life. The rapid development of this technology definitely brings positive and negative currents in its application. The higher the development, the greater the opportunity for negative impacts for irresponsible people. The utilization of technological developments in the financial sector is considered to greatly facilitate a person in carrying out economic activities. Armed with just one application, someone can make banking transfers, investments and their utilization in other economic activities. However, along with the ease and effectiveness of digital finance, there are also digital crimes that can harm many people in the banking world such as physing, malware, ransomware and so on. This type of research is a normative juridical research that focuses on laws and regulations to provide legal reformulation related to digital financial security finance to strengthen the defense of financial system protection in the digital sector which is very much needed in this increasingly sophisticated modern era.